In vitro antimicrobial effects of chitosan on microcosm biofilms of oral candidiasis - Araujo, Heitor Ceolin [UNESP]; Ramírez Carmona, Wilmer [UNESP]; Sato, Camila; dos Santos Oliveira, Marcelo [UNESP]; Alves, Guilherme dos Santos Gomes; Morato, Deborah Nunes; Pessan, Juliano Pelim [UNESP]; Monteiro, Douglas Roberto [UNESP] (Elsevier, 2022)
Objective: This study assessed the effects of chitosan (CS) on microcosm biofilms derived from saliva of patients with Candida-associated denture stomatitis. Methods: Five removable denture wearers with denture stomatitis were included in the study. The minimum inhibitory concentration (MIC) of CS against clinical isolates of Candida albicans was determined according to the broth microdilution method. Pooled saliva from the donors was used as an inoculum for the formation of biofilms, which were developed during 72 h on acrylic surfaces in the Amsterdam Active Attachment model. The biofilms were then treated with different concentrations of CS, and the antibiofilm effects were evaluated through the quantification of colony-forming units (CFUs), total biomass (TB), metabolic activity (MA), lactic acid production (LAP), and cell viability (by confocal laser scanning microscopy). Chlorhexidine, miconazole, and nystatin were tested as positive controls, while the negative control (NC) was the untreated biofilm. Data were analyzed by 1-way ANOVA and Fischer LSD's post hoc test (α=0.05). Results: MIC values of CS ranged from 500 to 800 µg/mL. For CFUs, 2500 µg/mL CS was the most effective treatment in reducing total anaerobes, mutans streptococci, and Lactobacillus spp., significantly differing from the controls. For C. albicans CFUs, CS and positive controls did not differ from each other but led to significant reductions compared to NC. Regarding TB, MA, LAP, and cell viability, 2500 µg/mL CS promoted the greatest reductions compared to NC. Conclusion: CS has similar or superior effects to conventional active principles on important parameters of oral candidiasis microcosm biofilms. Clinical Relevance: The antibiofilm effects of CS show that this compound has great potential to improve the clinical condition of denture stomatitis patients, and formulations containing this natural polymer could be useful for controlling oral candidiasis.
Keywords: Antimicrobials; Biofilms; Candida; Chitosan; Oral candidiasis